DCBLD1 Overexpression Is Associated With a Poor Prognosis in Head and Neck Squamous Cell Carcinoma - Fu, Ling-ling; Yan, Ming; Ma, Min-Xian; Luo, Yi; Shao, Min; Gosau, Martin; Friedrich, Reinhard E.; Vollkommer, Tobias; Feng, Hong-chao; Smeets, Ralf (Frontiers in Immunology, 2022)
Background: DCBLD1 is highly expressed in several kinds of cancer and could play a potential prognostic factor. However, the prognostic value and immune infiltration in head and neck squamous cell carcinoma remain unclear and need further research. Materials and Methods: DCBLD1 expression and clinical information were obtained from The Cancer Genome Atlas (TCGA) database. The mRNA level in cell lines (SCC25, CAL27) and gingival fibroblasts were detected by quantitative PCR. Cox regression analysis was used to evaluate the prognostic values of DCBLD1 and clinical data in HNSCC, a nomogram was also established to predict the impact of DCBLD1 on prognosis based on Cox multivariate results. The methylation level of DCBLD1 in HNSC and its prognosis were analyzed in UALACN and MethSurv. Gene set enrichment analysis (GSEA) and single sample GSEA (ssGSEA) were used to explore the potential biological functions of DCBLD1. Results: The mRNA and protein expression levels of DCBLD1 were highly expressed in HNSCC tissue and cell lines. The Cox analyses demonstrate that highly-expressed DCBLD1 is an independent prognosis marker(P<0.05). ROC curve analysis showed that performances of DCBLD1(area under the ROC curve 0.948, sensitivity 93.2%, specificity 84.7%). The methylation was increased in HNSCC patients compared with normal subjects(P<0.05) and was associated with poor prognosis at sites cg27642470 and cg21104965. Additionally, DCBLD1 expression is poorly associated with immune cell infiltration and immunological checkpoints PD-L1 and TIM-3. Conclusion: In head and neck squamous cell carcinoma, DCBLD1 is overexpressed, associated with poor patient prognosis. The detailed underlying mechanism merits further research.